Protective effects of ethyl pyruvate on sperm quality in cyclophosphamide treated mice - Zahra Bakhtiary; Rasoul Shahrooz; Abbas Ahmadi; Leila Zarei (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: One of the affecting factors in disturbance process of spermatogenesis is chemotherapeutic-induced oxidative stress resulted from cyclophosphamide (CP) treatment which leads to diminished sperm quality via interference in spermatogenesis process. Objective: This study was conducted to investigate the effects of ethyl pyruvate (EP) in reducing the CP-induced side effects on reproductive system. Materials and Methods: 24 mature male mice were randomly divided into 3 equal groups and were undergone therapy for 35 days. Control group received normal saline (0.1 ml/day, IP). CP group were injected CP (15 mg/kg/week, IP) and CP+EP group received EP (40 mg/kg/day, IP) as well as CP. In the end of the treatment period, the mice were euthanized by cervical dislocation. Then, the epididymis was incubated with CO2 in a human tubal fluid medium (1 ml) for half an hour in order to float sperm. Then, the number, motility, viability (eosin-nigrosin staining), DNA breakage (acridine orange staining), nucleus maturity, and sperm morphology (aniline blue staining) were analyzed. Results: The average (15.87±1.28), motility (35.77±2.75), viability (40±3.03), nucleus maturity (36±2.79) and sperm morphology (61.75±0.85) were decreased significantly in CP group in comparison with control and EP groups, whereas EP caused significant increase of these parameters. Also, the percentage of DNA damage was increased significantly in CP group (41.75±3.75) in comparison with control (2±0.71) and EP groups (22.5±4.13). Conclusion: The results of this study revealed ameliorating effects of EP on sperm quality of CP treated animals.